Complete genome sequence of a novel hypovirus infecting Phomopsis longicolla - Koloniuk, Igor; El-Habbak, Mohamed H; Petrzik, Karel; Ghabrial, Said A (Archives of virology, 2014)
The complete nucleotide sequence and genome organization of a hypovirus from the isolate ME711 of Phomopsis longicolla was determined and compared to sequences of members of the family Hypoviridae. The genome of the hypovirus, tentatively named Phomopsis longicolla hypovirus 1 (PlHV1-ME711), was determined to be 9760 nucleotides long, excluding the 3' poly (A) tail. The genome contains a single large open reading frame (ORF) encoding a polyprotein designated as P307. Its genomic organization is typical of members of the proposed genus Betahypovirus (Yaegashi et al. in Virus Res 165:143-50, 2012).
Keywords: RNA-viry; genom virový; Phylogeny; Ascomycota; Genome, Viral; Molecular Sequence Data; molekulární sekvence - údaje; fylogeneze; RNA Viruses; Viral Proteins; virové proteiny